2020
DOI: 10.1007/s00702-020-02260-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism after radiation exposure: brief narrative review

Abstract: The thyroid gland is among the organs at the greatest risk of cancer from ionizing radiation. Epidemiological evidence from survivors of radiation therapy, atomic bombing, and the Chernobyl reactor accident, clearly shows that radiation exposure in childhood can cause thyroid cancer and benign thyroid nodules. Radiation exposure also may induce hypothyroidism and autoimmune reactions against the thyroid, but these effects are less well-documented. The literature includes only a few, methodologically weak anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…), resulting in external exposure. Subsequent inhalation of contaminated air and ingestion of contaminated food and potable water can lead to internal radiation exposure and absorption of radioactive iodine, which primarily concerns the thyroid gland, being responsible of increased risk of thyroid alterations ( 70 ). Thus, there is no doubt that the thyroid gland is one of the most sensitive organs to, and at the highest risk of, cancer from ionizing radiation.…”
Section: Radioactive Iodine and Thyroidmentioning
confidence: 99%
See 1 more Smart Citation
“…), resulting in external exposure. Subsequent inhalation of contaminated air and ingestion of contaminated food and potable water can lead to internal radiation exposure and absorption of radioactive iodine, which primarily concerns the thyroid gland, being responsible of increased risk of thyroid alterations ( 70 ). Thus, there is no doubt that the thyroid gland is one of the most sensitive organs to, and at the highest risk of, cancer from ionizing radiation.…”
Section: Radioactive Iodine and Thyroidmentioning
confidence: 99%
“…Even in later studies ( 70 ), for example in the population affected by radioiodine emissions after the Chernobyl NPP accident, it has been suggested that for any community with large radioiodine exposure, hypothyroidism in children is a likely event, and if found, can easily be treated. Therefore, it is useful to implement targeted screening tests for such populations.…”
Section: Radioactive Iodine and Thyroidmentioning
confidence: 99%
“…The thyroid gland is known to be more susceptible to autoimmune attacks than any other organ ( 62 ). Hypothyroidism often occurs after hemithyroidectomy, radioiodine therapy, and neck radiotherapy ( 15 , 63 ). Whether thyroid IRAEs have the same mechanism as AITDs, warrants further elucidation.…”
Section: Mechanism Of Icis-related Thyroid Dysfunctionmentioning
confidence: 99%
“…Radiation can impair the thyroid gland via interfering with the mitosis of thyroid cells, disrupting the blood supply to the thyroid, and triggering autoimmunity characterized by the increased expression of anti-TPO Abs and anti-Tg Abs. Beyond the well-established elevated risk for external beam radiotherapy (EBRT)-induced hypothyroidism in cHL survivors more than 25 years after exposure to EBRT [ 133 ], radiotherapy in the form of TBI can cause permanent or transient hypothyroidism. A higher incidence of TBI-induced hypothyroidism has been related to a single dose of TBI (46–48%) compared to fractionated TBI (15–16%).…”
Section: Is There a Distinguishing Feature Of Ir Thyroid Disorders In The Setting Of Hematological Cancers Compared To Solid Tumors That mentioning
confidence: 99%